THE DIGITAL AGE AND THE EVOLUTION OF SOCIAL ECONOMY LAW: AN ANALYSIS OF THE LITERATURE AND ITS IMPACT ON THE FUTURE OF PUBLIC POLICY - Gunawan Widjaja (CV. Adiba Aisha Amira, 2024)
This research analyses relevant literature to identify key changes in copyright regulation, data protection and digital market policies. The analysis shows that the digital age presents new challenges and opportunities that require adaptive responses from legal systems and public policies. The impact of these changes includes the need to update and develop a more responsive regulatory framework that can not only accommodate technological innovation but also protect the public interest and ensure fair competition. This research highlights the importance of collaboration between policymakers, academics and legal practitioners to create policies that support sustainable economic and social development in the face of digital transformation.